1952
DOI: 10.1172/jci102600
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal Variation in the Urinary Excretion of Neutral Lipid-Soluble Reducing Steroids in Congestive Cardiac Failure and Cirrhosis of the Liver With Ascites 12

Abstract: Pincus and his collaborators (1-4) have demonstrated that there is a normal cycle of excretion of neutral, lipid-soluble reducing steroids which has a maximum between 7 a.m. and 11 a.m., decreases during the afternoon, and is at a minimum during the night. This corresponds to the normal excretory cycle of other urinary constituents (5-13). It has also been shown that in congestive cardiac failure (14, 15) and in cirrhosis of the liver with ascites (16) there is a reversed diurnal cycle of water and sodium excr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
1

Year Published

1953
1953
1967
1967

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 7 publications
0
2
1
Order By: Relevance
“…These results do not agree with those of other workers (16)(17)(18)(19)(20) who measured urinary corticoids by less specific methods. Although the ACTHinduced rise in the plasma 17-hydroxycorticosteroid level in the patients with liver disease was of the same magnitude as in the normal subjects, this implies a decreased adrenocortical secretion of 17-hydroxycorticosterone since its removal was impaired.…”
Section: Discussioncontrasting
confidence: 96%
“…These results do not agree with those of other workers (16)(17)(18)(19)(20) who measured urinary corticoids by less specific methods. Although the ACTHinduced rise in the plasma 17-hydroxycorticosteroid level in the patients with liver disease was of the same magnitude as in the normal subjects, this implies a decreased adrenocortical secretion of 17-hydroxycorticosterone since its removal was impaired.…”
Section: Discussioncontrasting
confidence: 96%
“…Goldman and Bassett (12) noted that the excretion of neutral lipidsoluble reducing steroids was proportional to the excretion of creatinine in their study of patients with cirrhosis and congestive heart failure and suggested that the excretion of corticosteroids may be proportional to the filtration rate. As no information is available at present regarding the filtrability of adrenal corticoids through the glomerular membrane, it is not possible to decide whether the changes in hormone excretion were due to changes in the amount filtered, or in tubular reabsorption or tubular secretion or hormone.…”
Section: Discussionmentioning
confidence: 99%
“…Although urine levels of "corticoids" have been reported to be normal or elevated in acute hepatitis (21) and cirrhosis (21,23,25,(29)(30)(31), the data in these studies are difficult to interpret because of the nonspecific methods of assay used. Brown,320 Willardson, Samuels and Tyler (32), using a more reliable assay method, found the urinary corticoids to be low in cirrhosis.…”
mentioning
confidence: 99%